1990
DOI: 10.1128/jb.172.8.4543-4548.1990
|View full text |Cite
|
Sign up to set email alerts
|

Plus-origin mapping of single-stranded DNA plasmid pE194 and nick site homologies with other plasmids

Abstract: Staphylococcus aureus plasmid pE194 manifests a natural thermosensitivity for replication and can be established in several species, both gram positive and gram negative, thus making it attractive for use as a delivery vector. Like most characterized plasmids of gram-positive bacteria, pE194 generates single-stranded DNA. The direction of pE194 replication is clockwise, as determined by the strandedness of free single-stranded DNA. Significant homology exists between a 50-base-pair sequence in the origin of pE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The pLS1 family of plasmids includes 10 replicons (9, 10), to which recently described plasmid pCI411 (5) should be added. The Rep nick site has been unequivocally determined for pLS1 (6,20) and genetically shown for pE194 (30). With these two exceptions, little is known about the leading-strand initiation and control region of the other members of the family, except for the information derived from sequence homologies.…”
Section: Resultsmentioning
confidence: 99%
“…The pLS1 family of plasmids includes 10 replicons (9, 10), to which recently described plasmid pCI411 (5) should be added. The Rep nick site has been unequivocally determined for pLS1 (6,20) and genetically shown for pE194 (30). With these two exceptions, little is known about the leading-strand initiation and control region of the other members of the family, except for the information derived from sequence homologies.…”
Section: Resultsmentioning
confidence: 99%
“…In a unit-length circular molecule, initiation and termination of ssDNA synthesis should occur at the same site within the plus-strand origin of replication. If two plus-strand origins of replication are present in the same molecule, as is the case in molecules containing tandem viral genome repeats, plus-strand synthesis may initiate at one origin and terminate at the other (19)(20)(21)(22). Single-strand replication from a molecule containing tandem genome repeats derived from different viral strains is predicted to generate unit-length progeny genomes of a single predominant genotype.…”
mentioning
confidence: 99%
“…The SS DNA is then converted to the double-stranded (DS) form utilizing the single-strand origin (SSO) (Baas and Jansz, 1988;Birch and Khan, 1992;Dempsey et al, 1995;Gruss et al, 1987). Previous studies have shown that the origin of replication contains sequences necessary for both the initiation and termination of RC replication (Dotto et al, 1984;Gros et al, 1987;Murray et al, 1989;Sozhamannan et al, 1990;Iordanescu and Projan, 1988;Zhao and Khan, 1996). While the sequences required for initiation and termination overlap, a larger region is required for the initiation step (Gros et al, 1987;Zhao and Khan, 1996).…”
Section: Introductionmentioning
confidence: 99%